how would I show that y'(t) = x(t) * h'(t) and y'(t) = x'(t) * h(t)(adsbygoogle = window.adsbygoogle || []).push({});

I know that in an LTI system y(t) = x(t) * h(t) = [itex]\int[/itex] x([itex]\tau[/itex]) * h(t-[itex]\tau[/itex]) from [itex]\infty[/itex] to -[itex]\infty[/itex]

But how would I go about trying to prove the first two equations?

**Physics Forums - The Fusion of Science and Community**

# Convolution Integral Properties

Know someone interested in this topic? Share a link to this question via email,
Google+,
Twitter, or
Facebook

- Similar discussions for: Convolution Integral Properties

Loading...

**Physics Forums - The Fusion of Science and Community**